How Scarlett Turns Online Word of Mouth Into Buying Desire Through The SOR Approach - Akhmad Edhy Aruman; Ananda Syifa Yustian Putri; Past Novel Larasaty; Latifa Ramonita (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2025)
Background: Consumer decisions to purchase cosmetic products in the digital era are increasingly influenced by electronic word of mouth (eWOM), rather than company promotions. However, limited research explains how eWOM shapes consumer perceptions into purchase intentions, primarily through psychological mechanisms in the context of products such as Scarlett, which carry strong personal and emotional values. Purpose: This study aims to examine the effect of eWOM on purchase intention by testing the mediating role of perceived functional value and perceived emotional value within the Stimulus–Organism–Response (SOR) approach. Method: This study employs a quantitative approach, using data collected via an online survey. The analysis was conducted using Partial Least Squares–Structural Equation Modeling (PLS-SEM). Findings: The results show that eWOM significantly influences purchase intention, both directly and through the mediation of perceived functional and emotional value. The model explains over 66% of the variance in consumer purchase intentions. Conclusions: Purchase decisions are formed by the interaction between external stimuli and the cognitive and emotional interpretation of personal values. Research Implication: Scarlett should strategically manage eWOM by encouraging authentic testimonials that are informative and emphasize the product’s emotional appeal and functional value.